2016
DOI: 10.21273/hortsci.51.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Yield Stability of Heirloom Dry Bean (Phaseolus vulgaris L.) Cultivars in Midwest Organic Production

Abstract: Heirloom dry bean (Phaseolus vulgaris L.) cultivars are distinct in their seed characteristics, although little information regarding their performance at the field scale in the Midwest is currently available. Demand for organic heirloom dry beans from direct-to-consumer markets in Minnesota motivated our examination of the crop’s suitability for local production. Heirloom cultivars were evaluated on the basis of yield and yield stability at four small-scale organic vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…+ (G × Env) was highly significant, indicating that genotypes considerable interacted with the eight environmental conditions. These results agree with those found by Pereira et al (2014) and Swegarden et al (2016).…”
Section: Estimates Of Stability Parameterssupporting
confidence: 94%
“…+ (G × Env) was highly significant, indicating that genotypes considerable interacted with the eight environmental conditions. These results agree with those found by Pereira et al (2014) and Swegarden et al (2016).…”
Section: Estimates Of Stability Parameterssupporting
confidence: 94%
“…For example, dry bean consumers may like to buy heirlooms with unique color patterns, which may be also sold at premium prices [26]. Swegarden et al [27] further indicated that both yield stability analysis and economic incentives suggest that heirloom dry bean cultivars-despite having a 44% lower average grain yield than commercial checks-may allow for diversifying production, differentiation in the market, and more attractive economic returns for their small-scale organic growers.…”
Section: Genetic Enhancement Using Heirlooms and Further Seed Supply mentioning
confidence: 99%
“…There is wide variation in productivity among heirloom cultivars when grown in organic farming systems. A few heirloom cultivars can compete with modern cultivars in organic systems, but almost no heirlooms can compete with modern cultivars under intensive production systems [26,27,[86][87][88]. However, heirloom cultivars possess great diversity in fruit and seed size, shape, and appearance.…”
Section: Retaining Culinary and Nutritional Traits And Improving Heirmentioning
confidence: 99%
“…This wide diversity -which is the main feature capturing the attention from consumers seeking unique, [24]. Swergarden et al [25] further indicated that both yield stability analysis and economic incentives suggest that heirloom dry bean cultivars -although having 44% lower average grain yield than commercial checks-may allow diversifying production, differentiating in the market, and keeping economic returns for their small-scale organic growers.…”
Section: Heirlooms and Sustainable Agriculturementioning
confidence: 99%
“…There is wide variation in productivity among heirloom cultivars when grown in organic farming systems. One a few heirlooms can compete with modern cultivars in organic systems, while almost no heirlooms can compete with modern cultivars under intensive production systems [24][25][82][83][84].…”
Section: Retaining Culinary and Nutritional Traits And Improving Heirmentioning
confidence: 99%